Postgraduate medical trainees at a Ugandan university perceive their clinical learning environment positively but differentially despite challenging circumstances: a cross-sectional stud - Alele, Paul E.; Kiptoo, Joshua; Hill‑Besinque, Kathleen (BMC Medical Education, 2023)
Purpose: The clinical learning environment is an essential component in health professions’ education. Data are scant on how postgraduate trainees in sub‑Saharan Africa perceive their medical school learning environments, and how those perceptions contribute to their engagement during training, their emotional wellbeing, and career aspirations. This study examined perceptions of postgraduate medical trainees (residents) in a resource‑limited setting, regarding their learning environment and explored perceptual contributions to their career engagement during training. The data reported contribute to understanding how clinical learning environments can be improved in low‑resource settings in Uganda and elsewhere. Methods: This study was done at the Faculty of Medicine of Mbarara University of Science and Technology in Uganda. We used a descriptive cross‑sectional design involving sequential mixed methods. Quantitative data were collected using the Postgraduate Hospital Educational Environment Measure (PHEEM). Qualitative data were collected using focus group discussions. Results: Ninety of the 113 eligible residents responded (79.6%). Of these, 62 (68.9%) were males, 51 (56.7%) were third‑year trainees, and the majority (40%) of the residents were aged between 30 and 34 years. Overall PHEEM scored 98.22 ± 38.09; Role Autonomy scored 34.25 ± 13.69, Teaching scored 39.7 ± 13.81, and Social Support scored 24.27 ± 10.59. Gender differences occurred in the perceptions of teaching and social support. Cronbach’s alpha coef‑ ficient was 0.94 for the overall PHEEM. Five major themes were identified from the qualitative data (trainee support, supervision environment, engagement with overall learning environment, preparation for future practice, and chal‑ lenges that impede training). Conclusions: Overall, this study suggests that postgraduate trainees at the institution perceived the clinical learning environment positively amidst challenges of limited resources. Trainees’ insights provided data that propose improve‑ ments on a number of domains in the learning environment.
Keywords: Postgraduate; Medical; Trainees; Learning; Environment; Career; Engagement; Uganda